Total Physical Response Storytelling in Early Childhood English Language Learning - Nensy Triristina; Elva Zakiyatul Fikria (Universitas Al-Hikmah Indonesia, 2025)
This study aims to provide a conceptual analysis of the application of Total Physical Response Storytelling (TPRS) in early childhood English language learning by examining its theoretical foundations, pedagogical components, and potential effectiveness for children aged 3–6 years. TPRS integrates Krashen’s comprehensible input principle, Asher’s Total Physical Response (TPR), and Ray’s narrative-based interaction to create a natural, enjoyable, and meaningful learning experience. A review of Scopus-indexed literature indicates that existing research on TPR and storytelling remains fragmented and predominantly focuses on vocabulary development or school-aged learners. None of the reviewed studies investigate TPRS comprehensively within early childhood settings, particularly regarding its effects on listening comprehension, language retention, and early storytelling skills. The analysis highlights that TPRS has strong potential to enhance vocabulary mastery, increase learning engagement, and build children’s confidence in language use through integrated movement and narrative activities. These findings position TPRS as a promising and developmentally appropriate approach for early childhood English instruction. The study further recommends future empirical research to validate the effectiveness of TPRS across diverse linguistic outcomes and to establish its role as a holistic framework for early language acquisition.